2015
DOI: 10.18388/abp.2014_832
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between serological markers of chronic C. pneumoniae and CMV infection and hsp60 in patients with atherosclerotic carotid stenosis

Abstract: A number of epidemiological studies conducted over the last decade indicate a relationship between specific pathogen infections and the development of atherosclerosis, although no pathogenetic pathways connecting these two have been determined. Recent reports support the role of heat shock proteins (HSPs) in atherogenesis. The HSPs are also believed to be a link between the infection and the development of atherosclerotic lesions. The aims of study: Immunohistochemical evaluation of carotid artery segments to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The hypothesis, put forward by A. Assinger, suggests a possible effect of the virus on the platelets. CMV is able to transmit activating signals that stimulate the migration of the leukocytes through the activation of TLR-2 platelet receptors [53].…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…The hypothesis, put forward by A. Assinger, suggests a possible effect of the virus on the platelets. CMV is able to transmit activating signals that stimulate the migration of the leukocytes through the activation of TLR-2 platelet receptors [53].…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…87 Evidence has demonstrated that bacterial and human HSP60 participate in the pathophysiology of atherosclerosis at different points of the disease progression elucidating its importance as a marker of disease and as a potential target for treatment. 9,10,[95][96][97] A study reported by Xu et al 95 might be one of the first papers where efforts were made to establish the role of HSPs in atherogenesis. Normocholesterolemic rabbits were immunized with HSP65, a major antigenic component of M. tuberculosis (mHSP65).…”
Section: Atherosclerosismentioning
confidence: 99%
“…However, if a sudden rupture of the plaque occurs, coronary artery occlusion can occur, causing a myocardial infarction 87 . Evidence has demonstrated that bacterial and human HSP60 participate in the pathophysiology of atherosclerosis at different points of the disease progression elucidating its importance as a marker of disease and as a potential target for treatment 9,10,95–97 …”
Section: Hsp60 In the Development Of Cvdsmentioning
confidence: 99%
See 2 more Smart Citations